Inovação no Ensino Superior: impacto da inovação pedagógica na estratégia de Catching Up em IES privadas brasileiras - Domingues, Fernando Moreira de Oliveira (2018)
Pedagogical Innovation comprises the adoption and dissemination of new practices, technologies and knowledge related to teaching and learning processes. Private higher education institutions (HEI) have seen in this type of innovation a strategy to remain relevant and an opportunity to maintain and develop competitive advantages in front of a market marked by competitiveness and large educational groups. These innovations can also contribute to the reduction of the technological gap that exists between Brazilian HEIs and those of developed countries, through a catching up innovation strategy. The main objective of this study was to investigate the extent to which the degree of adoption and dissemination of pedagogical innovation practices can contribute to the advancement of private Brazilian HEIs in this catching-up innovation strategy. For this, two measurement scales were developed and validated through psychometric procedures, then were applied to more than 850 teachers from 55 Brazilian HEIs. To analyze the data, the statistical technique of structural equations model (SEM) was adopted. The results allowed to support the hypothesis that there is a positive relationship between the adoption of pedagogical innovations and the degree of progress of the catching-up innovation strategy and thus to demonstrate that these innovations contribute to the development of innovative capacities by the HEI as a whole.